The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/18069657rbcs20150377
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemical and Physical Properties on an Inceptisol after Liming (Surface and Incorporated) Associated with Gypsum Application

Abstract: Inceptsoils have high aluminum contents, and amendments are required to ensure a satisfactory crop development. Liming is efficient in neutralizing Al 3+ , but when applied to the topsoil its action is restricted to the surface layers, and sometimes lime incorporation into the soil is recommendable. However, tillage may negatively alter physical soil properties. Thus, gypsum could be an alternative to increase Ca ) and incorporated into the soil by plowing and light harrowing. Gypsum was applied to the subplot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In general, liming effects are limited to the specific areas where the material is applied or incorporated for several reasons, including low solubility (Shainberg et al 1989) and soil texture. Pöttker and Ben (1998), Alleoni et al (2005), and Bortolanza and Klein (2016) demonstrated that after 3, 2.5 and 11 years the main effects of surface-applied lime to weathered soils under NT were limited to depths of 5, 10 and 5 cm, respectively (table 5). The trials described by those authors, as well as our field trial which was conducted under high annual precipitation (1500-mm) and with high lime rates (7.2 Mg/ha), were conducted on soils with high clay content (57%), and therefore increased resistance to lime movement (Conyers et al 2003).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In general, liming effects are limited to the specific areas where the material is applied or incorporated for several reasons, including low solubility (Shainberg et al 1989) and soil texture. Pöttker and Ben (1998), Alleoni et al (2005), and Bortolanza and Klein (2016) demonstrated that after 3, 2.5 and 11 years the main effects of surface-applied lime to weathered soils under NT were limited to depths of 5, 10 and 5 cm, respectively (table 5). The trials described by those authors, as well as our field trial which was conducted under high annual precipitation (1500-mm) and with high lime rates (7.2 Mg/ha), were conducted on soils with high clay content (57%), and therefore increased resistance to lime movement (Conyers et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Since lime moves very slowly into the soil profile, continued surface applications can cause chemical stratification (Bortolanza and Klein 2016, Martínez et al 2016, Barth et al 2018. Surface liming increases soil pH to levels above the optimum for crop growth (Fageria 2009) Excess lime can also affect soil biology (Paradelo et al 2015, Barth et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The action of limestone on soil pH-related improvements is already known due to the increase in OHin soil solution caused by the reaction of calcium carbonate with water, which contributes to the reduction in exchangeable Al activity and increases in Ca 2+ and Mg 2+ contents, promoting the development of the root system and, consequently, improvement in the absorption of the supplied nutrients, which is the most effective action in the most superficial soil layers. Bortolanza;Klein (2016) and Crusciol et al (2016) found an increase in topsoil pH after calcium carbonate application, which is related to the efficiency of the action in the topsoil due to its low mobility rate in the soil. Shamshuddin & Fauziah (2010) found results similar results to those found in this work.…”
Section: First Agricultural Cyclementioning
confidence: 96%